2016
DOI: 10.1371/journal.pone.0161672
|View full text |Cite|
|
Sign up to set email alerts
|

The Oncogene PDRG1 Is an Interaction Target of Methionine Adenosyltransferases

Abstract: Methionine adenosyltransferases MAT I and MAT III (encoded by Mat1a) catalyze S-adenosylmethionine synthesis in normal liver. Major hepatic diseases concur with reduced levels of this essential methyl donor, which are primarily due to an expression switch from Mat1a towards Mat2a. Additional changes in the association state and even in subcellular localization of these isoenzymes are also detected. All these alterations result in a reduced content of the moderate (MAT I) and high Vmax (MAT III) isoenzymes, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 78 publications
1
59
0
Order By: Relevance
“…Much of the phenotype of Mat1a KO mice was thought to be consequences of cytosolic SAM deficiency, although how SAM deficiency resulted in increased CYP2E1 expression was unclear. More recently, our study and others have shown that MATα1 can target the nuclear compartment where it can regulate gene expression by epigenetic mechanisms . In addition, we recently showed that MATα1 interacts directly with MAX and c‐MYC and negatively regulates E‐box‐driven reporter activity .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Much of the phenotype of Mat1a KO mice was thought to be consequences of cytosolic SAM deficiency, although how SAM deficiency resulted in increased CYP2E1 expression was unclear. More recently, our study and others have shown that MATα1 can target the nuclear compartment where it can regulate gene expression by epigenetic mechanisms . In addition, we recently showed that MATα1 interacts directly with MAX and c‐MYC and negatively regulates E‐box‐driven reporter activity .…”
Section: Discussionsupporting
confidence: 52%
“…More recently, our study and others have shown that MATα1 can target the nuclear compartment where it can regulate gene expression by epigenetic mechanisms. (26)(27)(28) In addition, we recently showed that MATα1 interacts directly with MAX and c-MYC and negatively regulates E-box-driven reporter activity. (19) This prompted us to investigate the MATα1 interactome, which revealed the unexpected high number of mitochondrial proteins, FIg.…”
Section: Discussionmentioning
confidence: 99%
“…In Artemia sinica, PDRG1 takes an essential role in diapause termination and regulation of cell cycle during early embryonic development [44] . By blocking the expression of pdrg1 in human colon cancer cells, cell growth reduced significantly [45] . Transcriptome based analysis indicated that the expression of p53 was significantly increased during diapause, and the contrary result was observed for pdrg1 in T.…”
Section: Comparative Analysis Of Genes Involved In Diapausementioning
confidence: 99%
“…12 Monomeric MATα1 is also found in nuclei and may be involved in other interactions. 12,13 Both MATα2 and MATβ subunits of the MATII isoenzyme have been detected in the cytoplasm and nucleus of mammalian cells. 14 Distinct functional interactions of these proteins exist based on their subcellular localization.…”
Section: Methionine Adenosyltransferasesmentioning
confidence: 99%
“…13 PDRG1 is an oncogene that is upregulated in cancers of the bladder, breast, and colon. 77 When PDGR1 binds to nuclear MATα1 there was a decrease in MAT activity and DNA was hypomethylated.…”
Section: Mats and Liver Dysfunctionmentioning
confidence: 99%